Hospital Management and Rehabilitation Medicine Integration: Challenges, Opportunities, and Future Directions - Ali Algarni, Mohammad; Khawjah, Rayan Fayez; Alsunaid, Abdullah Sunaid (Journal of Neonatal Surgery, 2025)
Increasing importance of hospital management rehabilitation medicine integration in offering holistic and patient center care. In this review paper, we review the complex relationship between administrative systems and rehabilitative services and how improving the interaction between these two systems can provide better treatment outcomes for patients, maximization of operational efficiency, and, ultimately, care continuity. The challenges highlighted by the study included limited resources, fragmented care models, absence of interdepartmental coordination, and inequity in access to rehabilitation services. This also underscores new opportunities that are arising—adoption of digital health technologies, promoting value-based care approaches, interdisciplinary teamwork, and policy changes that are conducive to integrative care practice. Based on a contemporary synthesis of the literature, case examples and international best practices, the paper provides a framework for a way forward in aligning hospital-based administration with rehabilitation approaches – including integrated care pathways, rehabilitation-led hospital processes and multi-professional training programmes. The results imply that innovation, cooperation, and a systems-thinking-wide approach is imperative for improvement at both the hospital and the individual patient rehabilitation levels as the healthcare landscape continues to evolve.